Comparison of the Relationship Between Sexual Function, Marital Adjustment, and Life Satisfaction in Diabetic and Non-Diabetic Women - Roghayeh Mehdipour-Rabori; Mahdieh Alinejad Dehsheakhi; Esmat Nouhi; Monirsadat Nematollahi (Shiraz University of Medical Sciences, 2020)
Background: Sexual function is important for diabetic women because it has a special effect on the quality of life. This study was conducted to compare the relationship of sexual function, marital adjustment, and life satisfaction between diabetic and non-diabetic women. Methods: This cross-sectional study was done in Kerman, Iran, from August 2018 to November 2019. The study sample included 300 diabetic women and 300 non-diabetic women. Data gathering tools included a demographic questionnaire, Rosen female sexual function index (FSFI), Spanier Dyadic Adjustment Scale (DAS), and Diner satisfaction with life scale. Data were analyzed through SPSS 15, using descriptive statistics, independent-t test, ANOVA, and Pearson tests. The significance level was considered 0.05. Results: The mean scores of marital adjustment, female sexual function index, and satisfaction with life scales in diabetic women were 90.98±23.33, 19.04±9.77, and 13.4±3.21; also, they were 120.34±33.34, 27.82±10.17, and 16.3±5.89 in non-diabetic women, respectively. Statistically significant differences were found between the scores of marital adjustment (P=0.001), female sexual function index (P=0.001), and satisfaction with life (P=0.001) in diabetic and non-diabetic women. The female sexual function index was correlated with life satisfaction and marital adjustment. Conclusion: Diabetic women experience sexual dysfunction because of their special condition, which negatively influences life satisfaction and marital adjustment. Healthcare providers should pay much more attention to this issue. They can provide educational packages on sexual issues for diabetic women. They should also support these women and their spouses to improve their quality of life.